The Effect of Multimedia-Based Education on Treatment Adherence, Self-Efficacy, and Readmission Rates in Post-Percutaneous Coronary Patients - Anita Setyawati; Ninik Yunitri; Yani Sofiani; Yuni Shahro; Rohman Azzam (GLOBAL HEALTH SCIENCE GROUP, 2026)
Patients with coronary heart disease (CHD) who undergo Percutaneous Coronary Intervention (PCI) experience faster recovery and a short hospital stay of up to three days. A short hospitalization process requires nursing interventions that are easily understood by patients and families, namely multimedia education, which aims to provide motivation so that patients become stronger when continuing their normal lives and returning to productivity. If patients do not carry out this behavior, the risk of myocardial infarction, stroke, and even death increases. to evaluate the effectiveness of multimedia-based education on medication adherence, self-efficacy and readmission rates of post PCI patients. Using quantitative research parallel Randomized controlled trial with a sample size of 100 people, by comparing the intervention group who received multimedia-based educational treatment and the control group who received standard therapy / leaflet at Gatot Soebroto Army Hospital. This study employed block randomization with a four-combination design in a 1:1 ratio. When all combinations were exhausted, the sequence returned to the initial combination. The randomization, therapists, data collectors, and data analysts were blinded to the study hypothesis. Data allocation was performed using random numbers, with odd and even numbers serving as the basis for assignment. Independent sample t-test in the intervention group on treatment compliance obtained a p-value of 0.441 with an effect size of 0.0168 (1.68%). While the measurement of self-efficacy is p-value 0.060 with an effect size of 0.1608 (16.08%). The Fisher Exact test showed that there was a significant difference between the two groups and the measurement of readmission rates decreased by 87.6% after being given multimedia education and a post-test of treatment adherence and self-efficacy. This study shows that the intervention of the effect of multimedia education on treatment compliance, self-efficacy and readmission rates in post PCI patients has a significant effect p-value> 0.05, there is an increase in treatment compliance, self-efficacy and a decrease in readmission rates in patients who have undergone PCI at RSPAD Gatot Soebroto.